(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
The purpose of this study is to address the lack of mental health services at Bestlink College of the Philippines, which may be affecting the psychological well-being of its students. The study aims to highlight the need for mental health services, including counseling, mental health awareness programs, and access to professional guidance. To achieve this, a descriptive research design was employed to collect data from respondents, assessing the need for these services and their potential benefits for students’ mental health and academic success. This study employed a quantitative research approach, with data collected through self-structured questionnaires designed for each group of respondents. The participants consisted of 100 Psychology students, with 25 students selected from each year level, resulting in a total sample size of 100 students. The study reveals that the majority of respondents are female, aged between 18 and 23. The influence of mental health services on mental health was rated with a composite mean of 3.57, while the overall well-being of psychology students had a mean of 3.53. Regarding academic performance, the composite mean was 3.56, indicating the positive impact of mental health services on students’ academic achievements. The benefits of implementing mental health services at Bestlink College were highlighted by a result of 3.65, suggesting that these services are accessible and play a significant role in supporting students’ mental well-being. Furthermore, the findings, with a composite mean of 3.62, provide a basis for designing a mental health awareness program that caters to the specific needs of the student population, enhancing the overall well-being of students pursuing psychology careers. The researchers recommend developing an awareness program to challenge the stigma surrounding mental health. These services will play a crucial role in assessing and improving the mental well-being of students, which in turn can positively influence their academic success. Implementing such initiatives will create a more supportive environment for students, fostering their overall well-being and academic achievement.